Beijing a survival guide to customs and etiquette - Jones, Kay; Pan, Anthony (Culture shock!, 2008)
Culture Shock! Beijing offers readers an insight into life within the capital and political centre of China. Home to more than 100,000 foreigners, it is no surprise that the city has been spawning modern buildings to accommodate the increasing economic activity. Ironically, many Beijinger's still do not have running water in their homes and most of them are not able to afford the numerous imported goods on sale at the spanking new shopping malls. Nevertheless, the people of Beijing boast a rich culture which has been preserved through a long line of dynasties. Go on a historical tour of the city
Keywords: Etiquette : China : Beijing; Beijing (China) : Social life and customs